(3EYeGd GdCYdGe ajef HhjY bHd GdGMJdGe ef edhc GdESdGe heGjJYdb HPdc ef GdcdGes - (3CHhYHO Gddg eMeO Hf YHO Gddg Hf SYjO GdSdeGfi GdZQfGWi GdCfOdSj, GdTgjQ HdSGf GdOjf Hf GdNWjH,J (B776 (3g` s
(3ChdgG (B:s
[ (3GdMeO ddg (B] (3GdPi HOC GdNdb Ke jYjOg s
(3BNQgG (B:s
(3Ke cGfJ HjYI GdYGeI EjGg jhe GdLeYI Gdehai YTQjf dTgQ QHjY GdChd s
(3GfXQ GdbSe GdChd HQbe (B44s
(3fSNI KGfjIs
(3hgh ai KdGKI CMRGAs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJGQjNs